Development of rice meal moth, Corcyra cephalonica (Stainton) on different food media - Ara, M Ismat; Haque, MA; Bari, MN; Ahmed, N; Islam, N (University Journal of Zoology, Rajshahi University, 2007)
Key words: Development; food media; Corcyra cephalonica Univ. j. zool. Rajshahi Univ. Vol.24, 2005. pp. 17-21